2014
DOI: 10.1016/j.psychres.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Associations between specific psychotic symptoms and specific childhood adversities are mediated by attachment styles: An analysis of the National Comorbidity Survey

Abstract: Accumulated evidence over the past decade consistently demonstrates a relationship between childhood adversity and psychosis in adulthood. There is some evidence of specific associations between childhood sexual abuse and hallucinations, and between insecure attachment and paranoia. Data from the National Comorbidity Survey were used in assessing whether current attachment styles influenced the association between adverse childhood experiences and psychotic symptoms in adulthood. Hallucinations and paranoid be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
167
4
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(187 citation statements)
references
References 52 publications
9
167
4
7
Order By: Relevance
“…For example, requiring substitute parental care is indicative of dysfunction, loss or stress in the family of origin and is associated with poorer long-term outcomes for adult adjustment, wellbeing and self-sufficiency (Buehler et al 2000). This result therefore lends further support to a growing body of literature indicating that attachment quality and disruptions in attachment behaviours (particularly that occurring in early childhood) can contribute to the development of adulthood psychosis (Read & Gumley, 2008;Harder, 2014;Sitko et al 2014).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, requiring substitute parental care is indicative of dysfunction, loss or stress in the family of origin and is associated with poorer long-term outcomes for adult adjustment, wellbeing and self-sufficiency (Buehler et al 2000). This result therefore lends further support to a growing body of literature indicating that attachment quality and disruptions in attachment behaviours (particularly that occurring in early childhood) can contribute to the development of adulthood psychosis (Read & Gumley, 2008;Harder, 2014;Sitko et al 2014).…”
Section: Discussionmentioning
confidence: 58%
“…However, although fostering/adoption was significantly associated with paranoid delusions, no relationship was found between CSA and any type of hallucination, or CPA and paranoid delusions. Thus the hypothesis (e.g., Bentall et al 2012;Shevlin et al 2014;Sitko et al 2014) that differential associations exist between these particular adversities and psychotic symptoms was only partially supported.…”
Section: Discussionmentioning
confidence: 98%
“…It has consistently been reported that psychosis is associated with a wide range of early adverse experiences . Some of these experiences of parental separation (Agid et al, 1999) neglect Sitko et al, 2014) victimisation through means of sexual abuse (Read et al, 2005), and of being unwanted at birth (Myhrman et al, 1996) may result in disruptions to the development of early secure attachment relationships, and may subsequently lead to the development of incoherent self/others beliefs that fluctuate over time.…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los modelos explicativos actuales de la paranoia consideran que las experiencias traumáticas juegan un papel fundamental en los orígenes de este trastorno (Bentall et al, 2001;Garety y Freeman, 1999). Asimismo, los estudios epidemiológicos han encontrado que los delirios de persecución están asociados con estilos de apego inseguro (Pickering, Simpson y Bentall, 2008;Sitko, Bentall, Shevlin y Sellwood, 2014). Es muy probable que acontecimientos traumáticos, a menudo de naturaleza interpersonal, o un apego inseguro condicionen las actitudes y el sistema de creencias del individuo, dando lugar a poblaciones vulnerables al despojarlos de mecanismos de protección universales.…”
Section: Discussionunclassified